Handedness and professional tennis - Holtzen, D. W. (International Journal of Neuroscience, 2000)
Based on the hypothesis that as a group left-handed (LH) people have better developed right hemispheres and therefore have better developed motor, attentional, and spatial functions than right-handed people (Geschwind, 1982; Geschwind and Galaburda, 1985a, 1985b; Nass and Gazzaniga, 1987), several studies have examined a possible association between left-handedness and superior tennis ability (cited in Annett, 1985; Azemar et al., 1983; Wood and Aggleton, 1989). The conflicting findings of these studies are due to flawed research designs, very limited data, and inadequate data analyses. In this study an estimated population rate of left-handedness for racket use (8.1%) was compared with rates found among professional tennis players; and highly successful competitors over a 32-year period were analyzed for handedness frequency. Results revealed that from 1968 through 1999 LH competitors were significantly over-represented among top ranking players (World Number One and Top Ten) and among Grand Slam finalists, including champions. Rates of left-handedness ranged from two to five times higher than expected in these highly successful players. However, no difference was found in the rate of left-handedness for racket use among male (N = 1,904; LH = 6.98%) or female (N = 533; LH = 7.69%) professional tennis players compared to the general population. These findings indirectly support the notion that LH people have neuroanatomically-based advantages in performing certain neurocognitive tasks, such as visuospatial and gross (whole body) visuomotor tasks. The present findings are also consistent with a nature/nurture model of cortical development and functioning (Casey, 1996).